2008
DOI: 10.1016/j.ijgo.2008.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Low‐molecular‐weight heparin versus intravenous immunoglobulin for recurrent abortion associated with antiphospholipid antibody syndrome

Abstract: LMW heparin plus low-dose aspirin resulted in a higher live birth rate than IVIG in the treatment of antiphospholipid antibody syndrome in women with recurrent abortion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(35 citation statements)
references
References 28 publications
0
34
0
1
Order By: Relevance
“…Dendrinos et al [40] showed consistent results (LMWH with LDA, 72.5% vs. IVIG, 39.5%; p =0.003). Although IVIG has a neutralizing effect for cytotoxic antibodies, the efficacy of IVIG in women with RPL and APAs is not clear based on the published clinical data.…”
Section: The Validity Of Ivig Therapy For Each Indicationmentioning
confidence: 73%
“…Dendrinos et al [40] showed consistent results (LMWH with LDA, 72.5% vs. IVIG, 39.5%; p =0.003). Although IVIG has a neutralizing effect for cytotoxic antibodies, the efficacy of IVIG in women with RPL and APAs is not clear based on the published clinical data.…”
Section: The Validity Of Ivig Therapy For Each Indicationmentioning
confidence: 73%
“…This treatment combination significantly reduces the miscarriage rate by 54%, and steroids associated with significant maternal, and fetal morbidity [72,73] .…”
Section: [Evidence 1++]mentioning
confidence: 98%
“…Steroids: Meta-analysis of RCTs reported that the only treatment that leads to significant increase in the live birth rate among women with APS is aspirin plus heparin, and steroids associated with significant maternal, and fetal morbidity [72,73] .…”
Section: [Evidence 1+]mentioning
confidence: 99%
“…Whilst steroids and aphaeresis procedures are currently considered additional therapies [72,73], data on the usefulness of IVIG in obstetric APS are conflicting [18][19][20][21][22][23][24][25][26][27][28][74][75][76]. The use of IVIG in pregnant APS women is rare and is generally considered a second-line treatment when other more standardized therapies have failed [77].…”
Section: Additional Treatments In High-risk Obstetric Apsmentioning
confidence: 99%
“…In addition, IVIG infusion was shown to prevent obstetric complications in APS animal models, possibly preventing the binding of antiphospholipid antibodies to the trophoblast [84]. It is interesting that IVIG resulted beneficial in most cases [18][19][20][21][22][23][24][25][26][27]78] when administered in addition to the first-line therapy, but it had only a slight [74] or no effect at all [75,76] when used alone as the first-line treatment. However, as the literature shows heterogeneous data with respect to IVIG dosing, timing of administration and concomitant treatment used (heparin, aspirin or steroids), it is difficult to draw well definite conclusions about IVIG benefits in obstetric APS.…”
Section: Additional Treatments In High-risk Obstetric Apsmentioning
confidence: 99%